Study of lipid profile in adult women with acne - da Cunha MG; Batista ALF; Macedo MS; Machado Filho CAS; Fonseca FLA (Dove Medical Press, 2015)
Marisa Gonzaga da Cunha,1 Anna Luiza Fonseca Batista,1 Marzia Silva Macedo,1 Carlos D’Aparecida Santos Machado Filho,1 Fernando Luiz Affonso Fonseca2 1Dermatology Department, Faculdade de Medicina do ABC (FMABC), Santo André, São Paulo, Brazil; 2Biological Sciences Department, Universidade Federal de São Paulo (UNIFESP), Diadema, São Paulo, Brazil Objective: The aim of this study was to establish the lipid profile of female patients with acne in the Acne-in-Adult-Women Ambulatory Care Clinic in order to observe the prevalence of dyslipidemia in those patients. Methods: This is a retrospective transversal study that evaluated the medical records of 416 patients who attended at the Acne-in-Adult-Women Ambulatory Care Clinic, at the Dermatology Department, Faculdade de Medicina do ABC, Santo André, São Paulo, Brazil, in the year 2012. Relevant data included age and clinical classification of acne. The lipid profile was analyzed according to the results of laboratory tests ordered during outpatient visits, which included total and fractionated cholesterol levels and triglycerides. Results: The epidemiological study sample was of 219 patients, with ages ranging from 21 to 61 years (mean of 32.23 years). The predominant clinical grade was papule-pustule acne (grade II) with 156 patients (71%). Regarding the lipid profile of the patients, there was a high increase in total cholesterol levels in 17.35% of the cases. High-density lipoprotein levels were low in 11.42% of the patients, with normal prevalence in 194 subjects. Low-density lipoprotein levels were normal in most patients (60.27%). Very-low-density lipoprotein values were normal in almost all patients (94.06%) and increased in only 13 patients (5.94%). Only 18 patients presented high levels of triglycerides (8.22%). Conclusion: The conclusion was that patients with grades II and III acne are more likely to have total cholesterol and low-density lipoprotein altered. A correct and early diagnosis can be an important measure for the prevention of the metabolic syndrome in these patients. Keywords: acne, hyperandrogenism, dyslipidemia, cholesterol, triglycerides